Parental Attention and Children’s Addiction to Online Games - Hidaayah, Nur; Kusnanto, Kusnanto; Yusuf, Ah; Santy, Wesiana Heris (International Journal of Psychosocial Rehabilitation, 2020)
Playing online games could promote children’s problem solving skill; however, parents need to protect their children when playing online games as it can be addictive. Limited studies have explained about parental attention and children’s addiction to online games. This study aimed to analyze the relationship between parental attention and children’s addiction to online games. An analytic observational study with a cross-sectional approach was used in this study. Seventy-five schoolchildren in grade 4 and 5 and their parents were chosen based on stratified random sampling. Data analysis was performed using the Rank Spearman correlation coefficient test with significance level of .05. The results showed that there was a strong relationship between parental attention and children’s addiction to online games (p < .05). Parental attention could reduce children’s addiction to online games. It is recommended that parents should be aware of negative effects of excessive online games.